STRATEGI MARKETING WISATA SYARIAH MELALUI INSTAGRAM - Danish Nur Amalina; Mashudi Anwar; Galuh Rachmawati (Reinforce: Journal of Sharia Management, 2022)
Tourism Marketing Strategy Through Instagram (Case Study of Blitar Chocolate Village). This type of research uses primary data and secondary data using qualitative research. The number of informants in this study amounted to 13 people (managers, employees, parking attendants, traders and visitors). Data collection techniques were carried out by means of interviews (interviews), and observations (observations), directly from respondents who were selected as samples. Based on the results obtained using qualitative analysis, it can be concluded in this study that the reasons why currently switching ways from conventional methods to Instagram marketing are, firstly because of technological advances, consumers are more inclined to use Instagram social media, secondly by using social media marketing in particular. Instagram can reduce prices in marketing financing, thirdly by utilizing influencers to further improve marketing on Instagram, and have a positive impact on the progress of Chocolate Village, lastly, the role of the variable place in the marketing mix can make visitors come back to Chocolate Village because Chocolate Village provides and presents an attractive place atmosphere for consumers and the price is also in accordance with the consumer's pocket. With advances in technology and promotional strategies can immediately move the hearts of consumers.